MODEL PEMBELAJARAN PROBLEM SOLVING BERBANTUAN KARTU SOAL DIGITAL UNTUK MENINGKATKAN AKTIVITAS BELAJAR DAN KEMAMPUAN PEMECAHAN MASALAH SISWA DI MTS MA’ARIF TIENG - Aini, Qurotu; Firdaus, Firdaus; Mulyani, Pamungkas Stiya (JRFES (Jurnal Riset Fisika Edukasi dan Sains), 2025)
Learning activities and problem-solving skills are crucial aspects in achieving national education goals that emphasize student independence and creativity. However, the dominant teaching methods in schools still focus on lectures, resulting in students' potential not being optimally developed. This study aims to evaluate the effectiveness of the Problem Solving learning model assisted by digital question cards in enhancing students' learning activities and problem-solving skills at MTs Ma’arif Tieng during the 2024/2025 academic year. The method used is a quantitative approach with a quasi-experimental design, where data is collected through observation sheets, pre-tests, and post-tests. The results indicate a significant improvement in students' learning activities and problem-solving skills, with t-test significance values of 0.000 and 0.001, respectively. This learning model proves to be quite effective in enhancing students' learning activities, with an average N-Gain score of 62% for learning activities and 40% for problem-solving skills, indicating it is less effective.